Emotional processes and their impact accompanying the competitor at the start of a sports event - Rybarczyk, Dominika; Klimczyk, Mariusz (Journal of Education, Health and Sport, 2017)
The aim of the work is to present information about the psychological and physical condition of athletes participating in sports competitions. Study was conducted among 33 active athletes. The research tool was an anonymous questionnaire consisting of 26 questions. The results showed that athletes are aware of the fact that the emotional state affects the outcome of the competition. It was also proved, that the strongest emotion accompanies them before the competition is the joy, satisfaction and pride. Majority of athletes experience moderate stress and excitation during the competitions. The biggest stress appears the most often in a few minutes before competition, the day before and a few hours before the competition. Athletes are people whose excitability is low. Potentially distracting external factors do not interfere with their performances and are often motivating. The most common motives for athletes are internal motives.